Communication patterns of the pahlawan women farmers group in the development of vegetable farming - Bulkis, Bulkis (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to analyze the communication patterns formed within the Pahlawan Women's Farmer Group (KWT) and its role in the development of vegetable farming businesses. Communication is an essential aspect in the planning, implementation, and evaluation of group programs. Using a qualitative approach, data were collected through interviews, observations, and documentation from KWT members. The results indicate that in the management of farming activities, there are two main communication patterns: two-way communication and multi-way communication. The two-way communication pattern is reflected in the interaction between the leader and group members, which is dialogical and allows for balanced information exchange. Meanwhile, the multi-way communication pattern is shown through open discussions between members and with external parties, such as agricultural extension workers. This communication occurs both directly and through media such as WhatsApp and posters. The effectiveness of communication is significantly influenced by the leader's skills, the education level of members, and the frequency of meetings. These findings highlight the importance of participatory and open communication patterns as a foundation for the success of women's farmer empowerment programs and the improvement of vegetable farming productivity.